2015
DOI: 10.1037/a0038498
|View full text |Cite
|
Sign up to set email alerts
|

The validity of the multi-informant approach to assessing child and adolescent mental health.

Abstract: Child and adolescent patients may display mental health concerns within some contexts and not others (e.g., home vs. school). Thus, understanding the specific contexts in which patients display concerns may assist mental health professionals in tailoring treatments to patients' needs. Consequently, clinical assessments often include reports from multiple informants who vary in the contexts in which they observe patients' behavior (e.g., patients, parents, teachers). Previous meta-analyses indicate that informa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

117
961
11
21

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 1,205 publications
(1,110 citation statements)
references
References 163 publications
(383 reference statements)
117
961
11
21
Order By: Relevance
“…However, the mean r for Externalizing of .55 was larger than that reported for population samples (.46). This Externalizing [ Internalizing r effect for clinical samples is consistent with Achenbach et al (1987) and De Los Reyes et al (2015), both of which included many studies with clinical samples. Cross-informant rs varied less across societies in the seven clinical samples (.42-.55) than in the 25 population samples (.17-.58).…”
Section: Cross-cultural Perspectives On Agreement Regarding Adolescensupporting
confidence: 75%
See 2 more Smart Citations
“…However, the mean r for Externalizing of .55 was larger than that reported for population samples (.46). This Externalizing [ Internalizing r effect for clinical samples is consistent with Achenbach et al (1987) and De Los Reyes et al (2015), both of which included many studies with clinical samples. Cross-informant rs varied less across societies in the seven clinical samples (.42-.55) than in the 25 population samples (.17-.58).…”
Section: Cross-cultural Perspectives On Agreement Regarding Adolescensupporting
confidence: 75%
“…Despite using 341 studies not analyzed in the 1987 review and employing somewhat different statistical procedures, De Los Reyes et al (2015) found essentially the same mean r of .28 between different kinds of informants observed by Achenbach et al (1987). Furthermore, they replicated the previous finding of better agreement for externalizing than internalizing problems, as well as the finding that mother-father agreement was better than agreement between informants who play different roles with the child (e.g., parent vs. teacher, parent vs. adolescent, etc.).…”
Section: Cross-informant Agreement Research: the First Generationmentioning
confidence: 68%
See 1 more Smart Citation
“…For adults, selfreports and clinician ratings may be the most often used sources, although over the last decade, researchers have increasingly leveraged reports from collateral informants, such as significant others of the adults being assessed (e.g., spouses, caregivers in the case of elderly adults; Achenbach 2006). Over 50 years of work across hundreds of investigations of informants' reports of children, adolescents, and adults indicates that mean cross-informant correspondence hovers in the low-to-moderate range (e.g., Pearson r's in the .20 s-.40 s; Achenbach et al 1987Achenbach et al , 2005De Los Reyes et al 2015b). However, correspondence does not remain uniform across informants.…”
Section: Ubiquity Of Adolescent-parent Reporting Discrepanciesmentioning
confidence: 99%
“…Using this approach, researchers gather reports from those involved in family interactions (e.g., parents and adolescents). Multiple informants' reports may also be augmented by data from other sources, such as independent observers' ratings of family interactions (e.g., level of warmth or hostility displayed within a laboratory-based family discussion task; De Los Reyes et al 2015b), or direct assessments of physiological processes as they manifest within relevant contexts (e.g., elevations in arousal or decreased physiological flexibility displayed during computer-based tasks, unstructured home observations, periods of social stress, or a resting period; Aldao and De Los Reyes 2015;De Los Reyes et al 2015a;De Los Reyes and Aldao 2015;Cohen et al 2015;Franklin et al 2015;Leitzke et al 2015;McLaughlin et al 2015;Youngstrom and De Los Reyes 2015). Further, a key focus of this approach involves collecting assessments of psychosocial outcomes commonly linked to family functioning, such as adolescent psychosocial functioning, which may also leverage multi-informant, multi-method measurement approaches (e.g., reports of adolescents' mental health from adolescents, parents, teachers, clinicians, and independent observers).…”
Section: Introductionmentioning
confidence: 99%